Sektionsausstellung GSMBA Bern. - Kunstmuseum Bern, Bern; Kunsthalle Bern, Bern (Bern : GSMBA, 1986)
Althaus, Andreas : Arni, Greti ; Arn-Grützner, Nell ; Bauer, Ellen ; Bärtschi, Marie ; Berger, Ueli ; Bezzola, Leonardo ; Blum, Kurt ; Böniger, Elsbeth ; Bracher, An ; Brignoni, Serge ; Brunner, Claire ; Brunner, Hansjürg ; Brunner, Urs ; Brüggemann, Karl ; Bundi, Stephan ; Burri, Ruth ; Bütikofer, Fritz ; Bütikofer Katharina ; Immenhauser, Verena ; Ciolina, Tonio ; Crippa, Luigi ; Daxelhofer, Vinzenz ; Deck, Leo ; Dickerhof, Urs ; Dieschmons, Heinz ; Dreyfuss-Wyler, Betty ; Duss, Arnold Werner ; Ebeling, Margarete ; Egger, Heinz ; Egli, Peter ; etc.
Sektionsausstellung GSMBA Bern, Kunstmuseum Bern / Kunsthalle Bern, 18. April bis 1. Juni 1986
boek